Ulla Hasager & Jonathan Friedman (eds.): Hawai’i - Return to Nationhood - Hviding, Edvard (Tidsskriftet Antropologi, 2019)
Ulla Hasager & Jonathan Friedman (eds.): Hawai’i - Return to Nationhood Anmeldes af Edvard Hviding